Grammar practice activities : - Ur, Penny (Cambridge University Press, 1988)
A detailed guide containing nearly two-hundred imaginalive and useful communicative grammar practice activities. The first part provides a general introduction to grammar teaching in the foreign language classroom, with particular reference to grammar practice. It suggests guidelines for the design of activities and includes a section of practical hints on effective classroom presentation. The second part provides nearly two-hundred communicative and gamelike practice activities for the main areas of English grammar. Teachers can copy these for immediate use in the classroom or use them as a guide to design their own practice materials.